The impact of motor and non-motor symptoms fluctuations on health-related quality of life in people with functional motor disorder - Jirásek, Martin; Sieger, Tomáš; Chaloupková, Gabriela; Nováková, Lucia; Sojka, Petr; Edwards, Mark J; Serranová, Tereza (Journal of psychosomatic research, 2025)
OBJECTIVE: To assess the effect of overall, between- and within-day subjectively rated fluctuations in motor and non-motor symptoms in people with functional motor disorder (FMD) on the health-related quality of life (HRQoL). BACKGROUND: FMD is a complex condition characterized by fluctuating motor and non-motor symptoms that may negatively impact HRQoL. METHODS: Seventy-seven patients (54 females, mean age 45.4 ± 10.4 years) with a clinically established diagnosis of FMD, including weakness, completed symptom diaries, rating the severity of motor and non-motor symptoms (i.e., pain, fatigue, mood, cognitive difficulties) on a 10-point numerical scale three times daily for seven consecutive days. HRQoL was assessed using the SF-36 questionnaire. For the analysis, fluctuation magnitude was defined in terms of the variability in self-reported symptom scores. RESULTS: The mental component of SF-36 was jointly predicted by the overall severity scores (t(74) = -3.61, P < 0.001) and overall general fluctuations (t(74) = -2.98, P = 0.004). The physical SF-36 was found to be related only to the overall symptom severity scores (t(74) = -7.09, P < 0.001), but not to the overall fluctuations. The assessment of the impact of different components showed that the mental component of SF-36 was significantly influenced by the combined effect of average fatigue (t(73) = -3.86, P < 0.001), between-day cognitive symptoms fluctuations (t(73) = -3.22, P = 0.002), and within-day mood fluctuations (t(73) = -2.48, P = 0.015). CONCLUSIONS: This study demonstrated the impact of self-reported symptom fluctuations across multiple motor and non-motor domains on mental but not physical HRQoL in FMD and highlighted the importance of assessing and managing fluctuations in clinical practice.
Keywords: bolest; Surveys and Questionnaires; Pain; Symptom variability; Humans; lidé středního věku; Quality of Life; Functional neurological disorder; Conversion Disorder; Female; dospělí; lidé; Fatigue; Mood; kvalita života; Fluctuations; průzkumy a dotazníky; Motor Disorders; Adult; konverzní poruchy; ženské pohlaví; stupeň závažnosti nemoci; Male; Middle Aged; únava; Severity of Illness Index; Quality of life; mužské pohlaví; Cognition; motorické poruchy